A calculus problem by Akshat Sharda

Calculus Level 4

P = 0 x 2 1 + x 4 d x Q = 0 x 1 + x 4 d x R = 0 1 1 + x 4 d x \begin{aligned} P & = \int^{\infty}_{0} \frac{x^2}{1+x^4}dx \\ Q & = \int^{\infty}_{0} \frac{x}{1+x^4}dx \\ R & = \int^{\infty}_{0} \dfrac{1}{1+x^4}dx \end{aligned}

Given the above, which of the following is true?

Q = π 4 , P = R , P 2 Q + R = π 2 2 Q=\frac{\pi}{4},P=R,P-\sqrt{2}Q+R=\frac{\pi}{2\sqrt{2}} Q = π 2 , P = R , P 2 Q + R = 0 Q=\frac{\pi}{2},P=R,P-\sqrt{2}Q+R=0 Q = π 4 , P R , P 2 Q + R = 0 Q=\frac{\pi}{4},P≠R,P-\sqrt{2}Q+R=0 Q = π 2 , P = R , P 2 Q + R = π 2 2 Q=\frac{\pi}{2},P=R,P-\sqrt{2}Q+R=\frac{\pi}{2\sqrt{2}}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Sep 13, 2017

Q = [ 1 2 tan 1 x 2 ] 0 = 1 4 π P R = 0 x 2 1 x 4 + 1 d x = 0 1 x 2 ( x + x 1 ) 2 2 d x = 0 d d x ( 1 2 2 ln ( x + x 1 2 x + x 1 + 2 ) ) d x = [ 1 2 2 ln ( x + x 1 2 x + x 1 2 ) ] 0 = 0 P + Q = 0 x 2 + 1 x 4 + 1 d x = 0 1 + x 2 ( x x 1 ) 2 + 2 d x = 0 d d x ( 1 2 tan 1 ( x x 1 2 ) ) d x = [ 1 2 tan 1 ( x x 1 2 ) ] 0 = π 2 \begin{aligned} Q & = \; \Big[\tfrac12 \tan^{-1}x^2\Big]_0^\infty \; =\; \tfrac14\pi \\ P - R & = \; \int_0^\infty \frac{x^2-1}{x^4+1}\,dx \; = \; \int_0^\infty \frac{1 - x^{-2}}{(x + x^{-1})^2-2}\,dx \; = \; \int_0^\infty \frac{d}{dx}\left(\frac{1}{2\sqrt{2}}\ln\left(\frac{x + x^{-1} - \sqrt{2}}{x + x^{-1} + \sqrt{2}}\right)\right)\,dx \\ & = \; \Big[\frac{1}{2\sqrt{2}}\ln\left(\frac{x + x^{-1} - \sqrt{2}}{x + x^{-1} - \sqrt{2}}\right)\Big]_0^\infty \; = \; 0 \\ P + Q & = \; \int_0^\infty \frac{x^2+1}{x^4+1}\,dx \; = \; \int_0^\infty \frac{1 + x^{-2}}{(x - x^{-1})^2+2}\,dx \; = \; \int_0^\infty \frac{d}{dx}\left(\frac{1}{\sqrt{2}}\tan^{-1}\left(\frac{x - x^{-1}}{\sqrt{2}}\right)\right)\,dx \\ & = \; \Big[\frac{1}{\sqrt{2}}\tan^{-1}\left(\frac{x - x^{-1}}{\sqrt{2}}\right)\Big]_0^\infty \; = \; \frac{\pi}{\sqrt{2}} \end{aligned} so that Q = 1 4 π Q = \tfrac14\pi , P = R P=R and P + R Q 2 = π 2 2 P+R - Q\sqrt{2} = \frac{\pi}{2\sqrt{2}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...